F x h fx h xh x h 2 multiply by the conjugate

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: − 5) = h h [steps are identical to A, but using “a” for”x”] 2 2 = [3(25 + 10h + h ) − 20 − 4h− 5] − (75 − 20 − 5) = [3h + 26h + 50] − (50) h = h 2 3h + 26h h(3h + 26) = = 3h + 26 h h VII. Examples using radical functions A. Given f (x ) = x 1. f ( x + h) − f(x) = h x+h − x . h 2. Multiply by the conjugate of the numerator to rationalize the numerator. ȹ ȹ ȹ ȹ = ȹ x + h − x ȹ ȹ x + h + x ȹ ȹ ȹ ȹ x + h + x ȹ h ȹ Ⱥ ȹ Ⱥ 3. = ( x + h) − x h( x + h + x ) = h h( x + h + x ) = 1 x+h + x B. Given f (x ) = x f ( 3 + h) − f(3) = h ȹ ȹ ȹ ȹ 3+h− 3 = ȹ 3 + h − 3 ȹ ȹ 3 + h + 3 ȹ ȹ ȹ ȹ 3 + h + 3 ȹ h h ȹ Ⱥ ȹ Ⱥ ( 3 + h) − 3 h 1 = = = h( 3 + h + 3 )...
View Full Document

Ask a homework question - tutors are online